Reinserção dos jovens autores de atos infracionais à sociedade: uma análise pelo olhar dos agentes transformadores da fundação CASA - Oliveira, Denilson Araujo de (2023)
This dissertation analyzes the contribution of the CASA Foundation to the reintegration of adolescents who committed an infraction into society, in compliance with or with a socio-educational measure carried out at the Institution, considering the positive and negative aspects of deprivation of liberty. The study adopts a realistic perspective and examines the potential for these young people to recover in society, especially when they return to their cities, from the contemporary perspective of the concept of Smart and Sustainable Cities (CIS). The research uses a qualitative and documentary approach, investigating the effects of socio-educational work in CASA Foundation service centers, with data presentation on the profile of the population of adolescents who committed infractions in the period from 2019 to 2023, in the municipalities that comprise the ABCD Paulista and application of a questionnaire to the Institution's employees. The study dialogues with the Sustainable Development Goals (SDGs) in the main correlation with: Eradication of Poverty (SDG 1); Health and Well-Being (SDG 3); Quality Education (SDG 4); Reduction of Inequalities (SDG 10); and Sustainable Cities and Communities (SDG 11), focusing on the juvenile population deprived of liberty in the state of São Paulo. The results demonstrate that in Brazil, the role of the family, society and the state is to act in the implementation and supervision of policies aimed at this part of the population, in the management of a socio-educational system with a more humanized and effective approach based on integral protection and adolescent development. Therefore, it is important to highlight that the social invisibility of young people who committed an infraction and of the CASA Foundation, as the executor of the socio-educational measure, is a problem that affects the entire society and its approach varies from one city to another. Therefore, the objective of this research is to analyze how the socio-educational measures applied by CASA Foundation contribute to the recovery of these young people.